2018
DOI: 10.1002/pat.4463
|View full text |Cite
|
Sign up to set email alerts
|

Improving piezoelectric and pyroelectric properties of electrospun PVDF nanofibers using nanofillers for energy harvesting application

Abstract: In this study, it was aimed to increase the piezoelectric and pyroelectric properties of electrospun polyvinylidene fluoride (PVDF) nanofibers simultaneously by using specific nanofillers. Graphene oxide (GO), graphene, and halloysite nanotubes with different concentrations (0, 0.05, 0.4, and 1.6% wt/wt) were combined with PVDF solution and were fabricated in the form of nanofibers through electrospinning. Pyroelectric properties of samples were measured by submerging sealed samples in hot water (360°K) and ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 46 publications
1
47
0
Order By: Relevance
“…From the schematic illustration, we can see that with the addition of BT to PVDF, stronger O-HF-C hydrogen atoms will form. It is believed to form due to the high polarity of hydroxyl groups, and as a result, oriented -CH 2 /-CF 2 dipoles favor orienting along with the F atoms closer to the BT nanoparticles, which is characteristic of the β-phase [ 108 ].…”
Section: Additives To Improve Piezoelectric Properties Of Electrosmentioning
confidence: 99%
See 2 more Smart Citations
“…From the schematic illustration, we can see that with the addition of BT to PVDF, stronger O-HF-C hydrogen atoms will form. It is believed to form due to the high polarity of hydroxyl groups, and as a result, oriented -CH 2 /-CF 2 dipoles favor orienting along with the F atoms closer to the BT nanoparticles, which is characteristic of the β-phase [ 108 ].…”
Section: Additives To Improve Piezoelectric Properties Of Electrosmentioning
confidence: 99%
“…Several research groups have been extensively investigating the effect of the addition of Gr in different forms on the mechanical, morphological, and electrical characteristics of electrospun PVDF nanofibers. In theory, pi bonds in Gr interact with fluorine atoms in PVDF, improving the formation of the β-phase [ 108 ].…”
Section: Additives To Improve Piezoelectric Properties Of Electrosmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbon atoms in graphene have a zig-zag structure which matches the zig-zag structure of the β-phase and therefore can be a strong nucleating agent [60]. Graphene oxide (GO) was more effective in enhancing piezoelectric and pyroelectric properties of PVDF than graphene [61]. Achaby et al [37] found that the α-peaks completely disappeared at the incorporation of 0.075 wt% GO and a solely β-phase was observed.…”
Section: Carbonaceous Nanofillersmentioning
confidence: 99%
“…In the past few years, the requirement of wearable electronics and wireless technologies is at the source of intensive study on electrical energy harvesting from the ambient environment. [1][2][3][4][5][6][7] This great advance in research has been brought on by new developments in low-power electronics and cordless detectors such as microelectromechanical systems (MEMS) devices. [8][9][10] There is no doubt that energy harvesting is an attractive approach for wide various self-powered microsystems.…”
Section: Introductionmentioning
confidence: 99%